Elderly care monitoring system with IoT application - Bong, Jia Cheng; Abdul Jamil, Muhammad Mahadi; Ambar, Radzi; Abd Wahab, Mohd Helmy (Springer Nature, 2020)
Falls among elderly can pose serious consequences such as injury or even fatal ones. Therefore, it is essential that fall are detected early and away to that is by using IoT platform. The authors have been developing a wearable device for elderly monitoring system utilizing accelerometer. The data from accelerometer is connected to an Internet-of-Things (IoT) platform called ThingSpeakTM. Based on IoT platform, elderly patients can be remotely monitored as long as the care providers have good internet access. The paper presents the experimental results of determining the sensitivity and specificity of the accelerometer used in the proposed system. This is the first step for developing an accurate data acquisition for monitoring purposes. Based on the experimental results, the average percentage for sensitivity obtained for this device is 73.3%, while the average for specificity obtained is 89.3%. Both sensitivity and specificity tests shows promising results which indicates that the device only has a fail rate of 26.7% and error rate of 10.7%.